A study of users’ perception of perceived risks on online banking adoption / Mohammad Firdaus Rosihan and Mohamad Salehan Samsudin - Rosihan, Mohammad Firdaus; Samsudin, Mohamad Salehan (Faculty of Business and Management, 2014)
This research is about a study of users’ perception of perceived risks on online banking. The independent variables which are security, privacy, times, performance and social are being identified and this study was conducted to examine whether these independent variables have significant influence on the perceived risk of online banking. In this research, the number of questionnaire collected is 150 questionnaires. The researchers use both primary and secondary data to obtain data. There are four methods that the researchers use to analyse data namely frequency, descriptive, reliability and regression. Based on the results from the analysed data, social risk has a high Cronbach's Alpha where it shows that the questions in the questionnaire are reliable. However, the independent variable that significantly influences the dependent variable is performance risk because the p-value of performance risk is 0.00 and hence the hypothesis is accepted.